2015
DOI: 10.1038/ncomms8910
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial ubiquitin ligase MARCH5 resolves MAVS aggregates during antiviral signalling

Abstract: Mitochondria serve as platforms for innate immunity. The mitochondrial antiviral signalling (MAVS) protein forms aggregates that elicit robust type-I interferon induction on viral infection, but persistent MAVS signalling leads to host immunopathology; it remains unknown how these signalling aggregates are resolved. Here we identify the mitochondria-resident E3 ligase, MARCH5, as a negative regulator of MAVS aggregates. March5+/− mice and MARCH5-deficient immune cells exhibit low viral replication and elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
134
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(135 citation statements)
references
References 56 publications
1
134
0
Order By: Relevance
“…For example, both Smurf1 and Smurf2 E3 ubiquitin ligases interact with MAVS and target MAVS for K48-linked ubiquitination (42,43). The mitochondrial ubiquitin ligase MARCH5 induces proteasome-mediated degradation of MAVS at Lys7 and Lys500 and modulates MAVS-mediated antiviral signaling (44). Until now, only the HECT domain E3 ligase AIP4 has been identified to be involved in virus-mediated MAVS degradation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, both Smurf1 and Smurf2 E3 ubiquitin ligases interact with MAVS and target MAVS for K48-linked ubiquitination (42,43). The mitochondrial ubiquitin ligase MARCH5 induces proteasome-mediated degradation of MAVS at Lys7 and Lys500 and modulates MAVS-mediated antiviral signaling (44). Until now, only the HECT domain E3 ligase AIP4 has been identified to be involved in virus-mediated MAVS degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with this, the level of MAVS was shown to decrease shortly after its activation through several distinct mechanisms. This includes Atg5-mediated autophagy of mitochondria (mitophagy) 54 , ubiquitin-mediated proteosomal degradation of MAVS (through the actions of E3 ligases, Smurf2 55 , March5 56 and pVHL 57 ). Other more complex regulatory mechanisms involving miniMAVS 58 , Trim25 59 and IRTKS 60 were also proposed.…”
Section: Rig-i-like Receptors (Rlrs): Rig-i and Mda5mentioning
confidence: 99%
“…It has been reported that the structure of a protein is associated with its function (50). Of note, Piasy binds to Rbp2 via its 101–218 aa (Fig.…”
Section: Discussionmentioning
confidence: 99%